ELAZIĞ MASALLARINDA İSLAM ÖNCESİ VE İSLAM SONRASI DİNİ MOTİFLERİN TESPİT VE TAHLİLİ - GÜNEŞ, MEHMET HALİM (Fırat Üniveristesi, 2005)
Türkler, İslam dinini kendi bünyelerine uygun gördüklerinden kendi istekleriyle bu dine bağlanıp yaşamışlardır. Zamanla Anadolu'ya gelip yerleşen Türkler, beraberlerinde İslam'a uygun örf ve adetlerini de aynen taşımışlardır. Bunlardan İslam'a aykırı olanları terk etmiş, bir kısmım da İslamileştirip yaşatmışlardır. Günümüz Elazığ ve yöresinde anlatılan masallarda Türk inancına ait İslam öncesi ve sonrası izleri ve bunlara ait pek çok motif vardır. Bu motiflerden bazılarını şekli değişse de özünü koruyarak günümüze kadar gelmiştir. Anahtar Kelimeler: Masal, motif, dini inanç, Elazığ.

As the Turkishs approved structure of themselves teh Islamic religion, they have believed this religion and lived. With time, the Turkishs that had come and settlerd in the Anatolia, have also brought exactly consuetudes and habits suitable for Islam. They leaved the cantrary ones to Islam and alived by making Islamic. In the fables told in Elazığ and the places near it, there are tracks belong ta Turkish reilgion before and after Islam and there are a lot of motives belong to these. Althovgh the some of them changed, the rest of them maintained to our today by keeping their essence. Keywords : Fable, motif, religious belief, Elazığ.
Determination and analysis of religious motives before and after Islam in fables of Elazığ
Keywords: Felsefe